(untitled) (Journal of Management & Business Studies, 2022)
The role played by gazelles in economic development processes is a topic of growing interest in the scientific and business community. Empirical evidence agrees that gazelles and fast-growing firms are innovative, transformative economic structures with capabilities to promote economic growth. This paper examines the role of a group of gazelle firms assisted in Arica that positively weigh the cost-benefit ratio of the Business Center program in Chile. This path poses an exercise in “appreciative theorizing” —as Richard Nelson (2018) calls it— and examines various factors of growth that cannot be explained by economic models in equilibrium.